2016
DOI: 10.1038/srep28734
|View full text |Cite
|
Sign up to set email alerts
|

New insights into salvianolic acid A action: Regulation of the TXNIP/NLRP3 and TXNIP/ChREBP pathways ameliorates HFD-induced NAFLD in rats

Abstract: Salvianolic acid A (SalA), one of the most efficacious polyphenol compounds extracted from Radix Salvia miltiorrhiza (Danshen), has been shown to possess many potential pharmacological activities. This study aimed to investigate whether SalA has hepatoprotective effects against high-fat diet (HFD)-induced non-alcoholic fatty liver disease (NAFLD) and to further explore the mechanism underlying this process. SalA treatment significantly attenuated HFD-induced obesity and liver injury, and markedly decreased lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 58 publications
3
73
0
Order By: Relevance
“…In this study, we identified that TXNIP was a direct target of miR‐335‐3p at its 3′‐UTR mRNA by bioinformatics, which was confirmed by luciferase reporter assays, and miR‐335‐3p overexpression suppressed NPC apoptosis and TXNIP expression at mRNA and protein levels, while silencing miR‐335‐3p led to an opposite effect. TXNIP, an endogenous inhibitor of thioredoxin, mediates NLRP3 inflammasome activation in various inflammatory diseases including, but not limited to diabetic retinopathy , rheumatoid arthritis (RA) , nonalcoholic fatty liver disease (NAFLD) . In this study, we confirmed that TXNIP expression at mRNA and protein levels was increased in IDD patients as compared to patients with spinal cord injury.…”
Section: Discussionmentioning
confidence: 89%
“…In this study, we identified that TXNIP was a direct target of miR‐335‐3p at its 3′‐UTR mRNA by bioinformatics, which was confirmed by luciferase reporter assays, and miR‐335‐3p overexpression suppressed NPC apoptosis and TXNIP expression at mRNA and protein levels, while silencing miR‐335‐3p led to an opposite effect. TXNIP, an endogenous inhibitor of thioredoxin, mediates NLRP3 inflammasome activation in various inflammatory diseases including, but not limited to diabetic retinopathy , rheumatoid arthritis (RA) , nonalcoholic fatty liver disease (NAFLD) . In this study, we confirmed that TXNIP expression at mRNA and protein levels was increased in IDD patients as compared to patients with spinal cord injury.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, NLRP3 deficiency had no effects on Cd‐induced TXNIP overexpression (data not shown), indicating that TXNIP overexpression occurs upstream of NLRP3 inflammasome activation after Cd exposure. In fact, TXNIP could directly activate the NLRP3 inflammasome under oxidative stress . Therefore, we speculate that targeting the TXNIP‐NLRP3 inflammasome pathway may be an effective therapeutic approach to attenuate Cd‐induced liver injury.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have indicated that HFD contributed to excessive production of reactive ROS [13] and, therefore, we investigated the effects of LDL on ROS levels of SW480, LoVo and RKO, using DCFH-DA fluorescence analysis. The results showed that all types of CRC cells treated with LDL exhibited significantly higher ROS levels compared with controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also suggested that HFD may contribute to inflammation and oxidative stress by causing excessive production of reactive oxygen species (ROS) [13]; moreover, both LDL and VLDL were shown to activate the extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MAPK) pathway [14]. ROS are a group of molecules and free radicals generated within cells through oxygen metabolism.…”
Section: Introductionmentioning
confidence: 99%